Importance to include the term superficial musculoaponeurotic system in medical subject headings and in the international anatomical nomenclature - Ferreira,Lydia Massako (2011)
PURPOSE: To investigate the relevance of the term superficial musculoaponeurotic system (SMAS) and demonstrate that this term is important enough to be added to the MeSH database and listed in International Anatomical Nomenclature. METHODS: Terms related to SMAS were selected from original articles retrieved from the ISI Web of Science and MEDLINE (PubMed) databases. Groups of terms were created to define a search strategy with high-sensitivity and restricted to scientific periodicals devoted to plastic surgery. This study included articles between January 1996 and May 2009, whose titles, abstracts, and keywords were searched for SMAS-related terms and all occurrences were recorded. RESULTS: A total of 126 original articles were retrieved from the main periodicals related to plastic surgery in the referred databases. Of these articles, 51.6% had SMAS-related terms in the abstract only, and 25.4% had SMAS-related terms in both the title and abstract. The term 'superficial musculoaponeurotic system' was present as a keyword in 19.8% of the articles. The most frequent terms were 'SMAS' (71.4%) and superficial musculoaponeurotic system (62.7%). CONCLUSION: The term SMAS refers to a structure relevant enough to start a discussion about indexing it as a keyword and as an official term in Terminologia Anatomica: International Anatomical Terminology.